2015
DOI: 10.1044/2015_jslhr-l-14-0134
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sentence Position, Allomorph, and Morpheme Type on Accurate Use of s-Related Morphemes by Children Who Are Hard of Hearing

Abstract: Purpose Production accuracy of s-related morphemes was examined in 3-year-olds with mild-to-severe hearing loss, focusing on perceptibility, articulation, and input frequency. Method Morphemes with /s/, /z/, and /ɪz/ as allomorphs (plural, possessive, third person singular –s, and auxiliary and copula ‘is’) were analyzed from language samples gathered from 51 children (ages: 2;10–3;8) who are hard of hearing (HH), all of whom used amplification. Articulation was assessed via the Goldman-Fristoe Test of Artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…This suggests that the reduction in audibility at 4 kHz from prescriptive target was significant enough to affect speech recognition in quiet and in background noise for children who wear HAs. This finding is consistent with earlier studies of speech perception (Stelmachowicz et al, 2001), phonological development (Moeller et al, 2007), word learning (Pittman, 2009), and morphosyntactic development (Koehlinger et al, 2015) that suggests that children with hearing loss who experience limited high-frequency bandwidth from their hearing aids may have delays in these domains. In some cases, frequency-dependent deviations from prescriptive target were present in children with overall RMS errors <5 dB, which highlights the importance of ensuring audibility at higher frequencies, even if the overall audibility meets the 5-dB RMS error criterion.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests that the reduction in audibility at 4 kHz from prescriptive target was significant enough to affect speech recognition in quiet and in background noise for children who wear HAs. This finding is consistent with earlier studies of speech perception (Stelmachowicz et al, 2001), phonological development (Moeller et al, 2007), word learning (Pittman, 2009), and morphosyntactic development (Koehlinger et al, 2015) that suggests that children with hearing loss who experience limited high-frequency bandwidth from their hearing aids may have delays in these domains. In some cases, frequency-dependent deviations from prescriptive target were present in children with overall RMS errors <5 dB, which highlights the importance of ensuring audibility at higher frequencies, even if the overall audibility meets the 5-dB RMS error criterion.…”
Section: Discussionsupporting
confidence: 91%
“…Children may have deviations from prescriptive target that cause audibility deficits only for specific input levels or specific frequency ranges, particularly frequencies above 4 kHz (Kimlinger et al, 2015). These high-frequency deviations could negatively impact their auditory access and language abilities (Koehlinger et al, 2015), but may not be apparent from measures of average speech audibility or when fitting errors are averaged into a single RMS error value across frequencies. An examination of the specific level-and frequency-dependent patterns of fitting errors might help to identify challenges in HA verification practices for children and better optimize audibility and comfort across different listening situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research has shown that daily HA use influences language outcomes in early school-age children with mild HL, particularly for morphosyntactic acquisition (Walker, Holte, et al, 2015). Access to high-frequency information is especially important because many English morphological markers consist of high-frequency, low-intensity phonemes (Koehlinger, Van Horne, & Moeller, 2013;Koehlinger, Van Horne, Oleson, McCreery, & Moeller, 2015;Stelmachowicz, Pittman, Hoover, & Lewis, 2002;Stelmachowicz, Pittman, Hoover, Lewis, & Moeller, 2004). Furthermore, children with mild HL will frequently encounter situations in which background noise and distance could have negative effects on the ability to learn language.…”
Section: Parental Attitudes Toward Intervention and Amplificationmentioning
confidence: 99%
“…In English, morphemes are often represented by phonemes that are challenging to hear [s, z, t], that may occur in sentence positions that lead to reduced amplitude, or that vary in their frequency of occurrence in the input (Hsieh et al, 1999). In the case of CHH, risk appears to relate to the reduced perceptibility of morphemes in running speech, differential effects of input frequency, and the limited bandwidth of HAs, which further reduces perceptibility and production of English morphemes realized as -s or –z (Kortekaas & Stelmachowicz 2000; Stelmachowicz et al 2002; Koehlinger et al 2015). …”
Section: Introductionmentioning
confidence: 99%